Effects of High Intakes of Fructose and Galactose, with or without Added Fructooligosaccharides, on Metabolic Factors, Inflammation, and Gut Integrity in a Rat Model. Issue 6 (25th February 2021) - Mhd Omar, Nor Adila; Frank, Jan; Kruger, Johanita; Dal Bello, Federica; Medana, Claudio; Collino, Massimo; Zamaratskaia, Galia; Michaelsson, Karl; Wolk, Alicja; Landberg, Rikard
Abstract : Scope: A high fructose and galactose intake show adverse metabolic effects in animal models and in humans, but it is yet unknown if addition of fermentable dietary fiber can mitigate such effects. This study investigate the effects of high intakes of fructose and galactose, with/without added fructooligosaccharides (FOS), on metabolic factors, inflammation, and gut integrity markers in rats. Methods and Results: Rats ( n = 6/group) receive different carbohydrates at isocaloric conditions for 12 weeks as follows: 1) starch (control), 2) fructose, 3) galactose, 4) starch + FOS (FOS control), 5) fructose + FOS, and 6) galactose + FOS, together with a high amount of n‐6 polyunsaturated fatty acids (n‐6 PUFA) in all diets except for in 7) starch + olive oil (negative control). The rats fed the galactose and galactose + FOS diets exhibit lower body weight than other groups. High‐galactose diets has more pronounced effects on metabolic factors and gut permeability than high‐fructose diets. High‐fructose diets show less pronounced effect on these selected markers. No differences in inflammatory markers are detected for any of the diets. Conclusions: The results suggest potential adverse effects of high galactose and fructose on metabolic factors and gut integrity markers, but not on inflammation. However, several mechanisms are at play, and general net effects are difficult to determine conclusively for the conditions tested. Abstract : High intake of simple sugars in the diet may evoke adverse metabolic and pro‐inflammatory responses, whereas a diet rich in dietary fiber such as fructooligosaccharides (FOS) is believed to have anti‐inflammatory effects that may reverse the adverse effects caused by simple sugars. This study investigate the effect of high carbohydrates diets, particularly high fructose and galactose with and without added fiber (FOS) on metabolic factors, inflammation, and gut integrity in a rat model. It is found that the diets affect several metabolic factors and gut integrity, but not inflammation.